Effect of vitamin or mineral supplementation on oxidation and quality traits of fresh and aged beef - Ramos, Jenifer Maira Lima (Universidade Federal de Viçosa, 2022)
This study was divided into two experiments. The first experiment with the use of fat-soluble vitamins (ADE) and/or water-soluble vitamins (biotin, niacin and thiamine) via diet in Nellore cattle. The second experiment with the use of vitamins AE and microminerals (Se, Mn, Zn and Cu) injected in crossbred cattle (¾ Angus, ¼ Nellore). Each of the two experiments originated a chapter of this thesis, totaling two chapters. In the first chapter, the effect of supplementation with a mix of B vitamins (biotin, niacin and thiamine), mix of vitamins (ADE) or a combination of these mixes on oxidation parameters, antioxidant status and quality of beef was evaluated. Nellore. Forty Nellore bulls, with a mean age of 8 ± 1 month and mean body weight of 261 ± 27.3 kg, were randomly assigned to four treatments: (a) without vitamin supplementation (Control); (b) vitamin B (B) mix supplementation; (c) mix supplementation of fat-soluble vitamins (ADE); and (d) combination of mixes (ADE + B). At the end of the 140-day period, the longissimus lumborum muscle was collected for analysis of meat quality, antioxidant enzyme activities and lipid oxidation at 1h, 24h, 196h and 360h postmortem. Supplementation with ADE and ADE+B increased intramuscular fat content, oxymyoglobin (OMb) and decreased metmyoglobin (MMb) at 196h and 360h postmortem, and decreased deoxymyoglobin (DMb) 196h postmortem, increased the Myofibrillar Fragmentation Index (MFI) 24h, 196h and 360h postmortem. In addition, ADE supplementation increased superoxide dismutase (SOD) and Ferric Antioxidant Reducing Power (FRAP), decreased glutathione peroxidase (GPx) and nitric oxide 24h postmortem, increased catalase and FRAP 196h postmortem, and increased FRAP and decreased malondialdehyde (MDA) 360 hours postmortem. In the second chapter, the effects of injectable supplementation of vitamins A and E and micro-minerals (Se, Mn, Zn and Cu) applied at weaning (D), castration (C) and pre- slaughter (PA) or their combination on meat quality, antioxidant status and lipid oxidation of crossbred cattle (¾ Angus ¼ Nellore). One hundred and twenty crossbred cattle, with a mean age of 7 ± 1 month and mean body weight of 304.58 ± 33 kg, were randomly assigned to six treatments: (N=20): (i) 000-Control (saline solution (SS) on D , C and PA; (ii) DCA - Vitamin- mineral complex (MVC) in D, C and PA; (iii) DC0 - MVC in D and C + SS in PA; (iv) D0A - MVC in D + SS in C + CVM in the PA; (v) 00A - SS in the D and C + CVM in the PA; (vi) 0CA– SS in the D + CVM in the C and PA. At the end of the period of 250 days, the collection was performed for the analyzes of meat quality, antioxidant enzyme activities and lipid oxidation in longissimus thoracis and lumborum muscle 1h, 24h, 196h and 360h postmortem. 192h and 360h postmortem. The shear force variable showed a difference 24h and 192h postmortem. Antioxidant activity (CAT and FRAP) and MDA showed a difference 1h postmortem. SOD and FRAP 24h postmortem, FRAP and MDA 192h postmortem and CAT and FRAP 360h postmortem. In the longissimus lumborum muscle, the Hue, MMb and OMb variables were different 24 hours postmortem. The variables a*, chroma and OMb showed a difference 192 hours postmortem and the variables a*, b* and chroma showed a difference 360h postmortem. FRAP showed difference 24h and 360h postmortem, GPx and SOD 360h postmortem. The use of CVM at least in PA reduces the oxidation of OMb to MMb and provides greater antioxidant status and decreased lipid oxidation. Keywords: Antioxidants. Colour. Myoglobin. Oxidation.

Este estudo foi dividido em dois experimentos. O primeiro experimento com a utilização de vitaminas lipossolúveis (ADE) e/ou hidrossolúveis (biotina, niacina e tiamina) via dieta em bovinos Nelore. O segundo experimento com a utilização de vitaminas AE e microminerais (Se, Mn, Zn e Cu) injetável em bovinos cruzados (¾ Angus, ¼ Nelore). Cada um dos dois experimentos originou um capítulo desta tese, totalizando dois capítulos. No primeiro capítulo avaliou-se o efeito da suplementação de um mix de vitaminas do complexo B (biotina, niacina e tiamina), mix de vitaminas (ADE) ou a combinação desses mix sobre parâmetros de oxidação, status antioxidante e qualidade da carne de bovinos Nelore. Quarenta tourinhos Nelore com idade média de 8 ± 1 meses e peso corporal médio de 261 ± 27,3 kg, foram distribuídos aleatoriamente em quatro tratamentos: (a) sem suplementação vitamínica (Controle); (b) suplementação mix de vitaminas B (B); (c) suplementação mix de vitaminas lipossolúveis (ADE); e (d) combinação dos mix (ADE + B). Ao final do período de 140 dias foi realizada a coleta do musculo longissimus lumborum para as análises de qualidade da carne, atividades de enzimas antioxidantes e oxidação lipídica 1h, 24h, 196h e 360h postmortem. A suplementação com ADE e ADE+B aumentou o teor de gordura intramuscular, a oximioglobina (OMb) e diminuiu a metamioglobina (MMb) aos 196h e 360h postmortem, e também diminuiu a desoximioglobina (DMb) 196h postmortem, aumentou o índice de fragmentação miofibrilar (IFM) 24h, 196h e 360h postmortem. Além disso, a suplementação com ADE aumentou a superóxido dismutase (SOD) e o Poder Antioxidante Redutor Férrico (FRAP), diminuiu a glutationa peroxidase (GPx) e o óxido nítrico 24h postmortem, aumentou a catalase e FRAP 196h postmortem, e aumentou FRAP e diminuiu malondialdeído (MDA) 360h postmortem. No segundo capítulo, avaliou-se os efeitos da suplementação injetável de vitaminas A e E e micro-minerais (Se, Mn, Zn e Cu), aplicados no desmame (D), castração (C) e pré-abate (PA) ou sua combinação, sobre a qualidade da carne, status antioxidante e oxidação lipídica de bovinos cruzados (¾ Angus ¼ Nelore). Cento e vinte bovinos cruzados com idade média de 7 ± 1 meses e peso corporal médio de 304.58 ± 33 kg, foram distribuídos aleatoriamente em seis tratamentos: (N=20): (i) 000- Controle (solução salina (SS) no D, C e PA; (ii) DCA - Complexo vitamínico-mineral (CVM) no D, C e PA; (iii) DC0 - CVM no D e C + SS no PA; (iv) D0A - CVM no D + SS na C + CVM no PA; (v) 00A - SS no D e C + CVM no PA; (vi) 0CA– SS no D + CVM na C e PA. Ao final do período de 250 dias foi realizada a coleta para as análises de qualidade da carne, atividades de enzimas antioxidantes e oxidação lipídica no músculo longissimus thoracis e lumborum 1h, 24h, 196h e 360h postmortem. No músculo longissimus thoracis, as variáveis a* e Hue apresentaram diferença 192h postmortem e a MMb em 192h e 360h postmortem. A variável força de cisalhamento apresentou diferença 24h e 192h postmortem. A atividade antioxidante (CAT e FRAP) e MDA apresentaram diferença 1h postmortem. SOD e FRAP 24h postmortem, FRAP e MDA 192h postmortem e CAT e FRAP 360h postmortem. No músculo longissimus lumborum, as variáveis Hue, MMb e OMb foram diferentes 24h postmortem. As variáveis a*, chroma e OMb apresentaram diferença 192h postmortem e as variáveis a*, b* e chroma apresentaram diferença 360h postmortem. FRAP apresentou diferença 24h e 360h postmortem, GPx e SOD 360h postmortem. A utilização de CVM ao menos no PA reduz a oxidação da OMb a MMb e proporciona maior status antioxidante e diminuição da oxidação lipídica. Palavras-chave: Antioxidantes. Coloração. Mioglobina. Oxidação.
Efeito da suplementação vitamínica ou mineral na oxidação e características de qualidade da carne fresca e maturada
Keywords: Nelore (Bovino) - Nutrição; Vitaminas na nutrição animal; Carne de boi - Qualidade; Antioxidantes; Cor dos alimentos; Mioglobina; Produção Animal